The effect of onion and garlic powders on growth performance, viability, intestine histomorphology, and some blood parameters in Chukar Partridge chicks - Harman, H; Eşki, HT; Ündağ, İ; Akbulut, K; Başer, E; Kırıkçı, K; Dönmez, HH (Journal of the Hellenic Veterinary Medical Society, 2024)
In the present study, a total of 270 chicks were divided into 6 main groups and 3 subgroups within 15 chicks in each subgroup. Except for the control group, 0,5% garlic, 0,5% onion, 1% onion, 1% garlic, and a mixture of 1% onion + 1% garlic powder were added to the diet of the study groups. According to the results of the study, there were no significant differences between the control and experimental groups in the body weight gain and feed consumption (P>0,05). In biochemical analyses, there were no significant differences between the groups in low density lipoprotein and cholesterol levels but significant differences were found in high density lipoprotein and malondialdehyde levels, especially in 1% onion powder (P<0,05). According to histological analysis, significant differences were found in villus length, crypt depth, and goblet cell count and the highest villus length was recorded in the 1% onion powder group (P<0,05). A significant statistical difference was found between all experimental groups and the control group in the viability and the highest rate was recorded in the 1% onion powder group (P<0,01). As a result, onion garlic powders increased the viability of chukar partridge chicks, which are quite difficult to breed. When all the data were examined, it was determined that the most beneficial supplementation was 1% onion powder.